Impact of physical activity on quality of life in patients with epilepsy in a developing country: A cross-sectional, survey-based study - Daniel San-Juan; Miguel Benjamín Cervera-Sánchez; Miguel Angel Morales-Morales; Emilio Israel Wong-Valenzuela; Dara Lizeth Torres-Rodríguez; Daniela Carolina Pimentel-Saona (eNeurologicalSci)
Rationale: Patients with epilepsy face different barriers based on ignorance and fear of themselves and others while exercising, this situation complicates attempts at exercise and promotes discrimination against patients. Physical activity has been associated with favorable results in the health of this population and can be used as a non-pharmacological treatment seeking to increase the health and improve living conditions of patients. Our study aims to explore how physical activity impacts quality-of-life perception in these patients. Methods: We performed a cross-sectional, survey-based study conducted at the outpatient Epilepsy Clinic in the National Institute of Neurology and Neurosurgery “Manuel Velasco Suárez”. Patients between 17 and 65 years of age and with an established diagnosis of epilepsy were considered for participation. A 31-item questionnaire was administered to all participants face-to-face or by telephone. The questions included in the survey were selected from the Global Physical Activity Questionnaire and the Quality of Life in Epilepsy Inventory to assess the level of exercise and perceived quality of life of participants. Descriptive and inferential Mann-Whitney U test statistical analysis was done using IBM SPSS Statistics 23.0 software. Results: Participants' mean age was 35.69 ± 11.93 years, 45 % were male and 55 % female. Significant differences were found in the domain of perceived quality of life in the self-reported physically active participants (p = 0.0256; 95 % IC: 1.00–15.22), with a mean score of 75.78 ± 16.64 in the active group vs. 67.66 ± 15.86 in the sedentary group. In those who complied with the exercise recommendations according to the WHO, there was significant evidence of improvement in the general quality of life (p = 0.0032; 95 % IC:4.9–23.9), with a mean score of 75.22 ± 15.92 in the active group vs. 60.76 ± 17.836 in the sedentary group. Conclusions: Physical activity is associated with a significant impact on how patients with epilepsy perceive their quality of life. In addition, it improves memory and concentration in the tasks they perform in their daily lives.